Clinical management of children with tic disorder: insights from therapeutic visits in China—a real-world study - Wang, Jing; Luo, Changyong; Wang, Zhendong; Liu, Tiegang; Bai, Chen; Wang, Yang; Tian, Yuanshuo; Li, Qianqian; Wang, Zhaoxin; Wu, Liqun; Wang, Sumei; Gu, Xiaohong (Frontiers in Pediatrics, 2024)
Objective This retrospective study aims to investigate the treatment of tic disorder (TD) in Dongfang Hospital affiliated with Beijing University of Chinese Medicine, explore its underlying mechanism, and provide valuable insights for future research and clinical management of TD. Methods The electronic medical records of children with TD, from 2015 to 2021, were extracted from the information system of Dongfang Hospital affiliated with Beijing University of Chinese Medicine. The clinical characteristics of TD, utilization patterns of Chinese herbal medicine and synthetic drugs in prescriptions, as well as their pharmacological effects, were statistically described and categorized. In addition, association rules and network pharmacology were employed to identify core prescriptions (CPs) and elucidate their microscopic molecular mechanisms in treating TD. Results The age range of the children was from 6 to 11 years, with a higher proportion of male participants than female ones. The average duration of treatment was 6 weeks. Regimen Z for the treatment of TD can be summarized as follows: Chinese herbal medicine [Saposhnikoviae Radix (FangFeng), Puerariae Lobatae Radix (GeGen), Uncariae Ramulus cum Uncis (GouTeng), Acori Tatarinowii Rhizoma (ShiChangPu), Chuanxiong Rhizoma (ChuanXiong)] and vitamins [lysine, inosite, and vitamin B12 oral solution] form the basic treatment, combined with immunomodulators, antibiotics, electrolyte-balancing agents, and antiallergic agents. CPs primarily exerted their effects through the modulation of gene expression (transcription), the immune system, and signal transduction pathways, with interleukin-4 and interleukin-13 pathways being particularly crucial. Among the lysine synthetic drugs used, inosite and vitamin B12 oral solution were the most frequently prescribed. Conclusion The regimen Z drug treatment holds significant importance in the field, as it exerts its therapeutic effects through a multitude of pathways and intricate interventions. Chinese herbal medicine primarily regulates immune system–related pathways, while synthetic drugs predominantly consist of vitamins.